QHWM of the orthogonal and symplectic types lie subalgebras of the lie algebra of the matrix quantum pseudo-differential operators - Batistelli, Karina Haydeé (2018)
Fil: Batistelli, Karina Haydeé. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.